2008
DOI: 10.1007/s00438-008-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-conjugating enzyme (Sce) and FK506-binding protein (FKBP) encoding rice (Oryza sativa L.) genes: genome-wide analysis, expression studies and evidence for their involvement in abiotic stress response

Abstract: We report an in-depth characterization of two major stress proteins namely SUMO-conjugating enzyme (Sce) and peptidyl prolyl cis-trans isomerase (PPIase) in rice (Oryza sativa L.). Sce mediates addition of SUMO group to various cell proteins, through process referred to as SUMOylation. Rice nuclear genome has two putative genes encoding the Sce protein (OsSce1 and OsSce2). PCR-amplified full-length OsSce1 cDNA functionally complemented the growth defect in yeast cells lacking the equivalent Ubc9 protein (ScDel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 64 publications
4
60
2
1
Order By: Relevance
“…PCR using primers specific for the first 550 bp of Gus gene was performed to confirm the integration of transfer DNA (T-DNA) in the transgenic plants. Transient assays in onion cells were performed as described earlier (Nigam et al 2008). 2kbPro OsClpB-cyt ::Gus construct was used in this experiment.…”
Section: Plasmid Construction For Plant Transformationmentioning
confidence: 99%
“…PCR using primers specific for the first 550 bp of Gus gene was performed to confirm the integration of transfer DNA (T-DNA) in the transgenic plants. Transient assays in onion cells were performed as described earlier (Nigam et al 2008). 2kbPro OsClpB-cyt ::Gus construct was used in this experiment.…”
Section: Plasmid Construction For Plant Transformationmentioning
confidence: 99%
“…A technical exception to this rule is provided by several land plants that have undergone various rounds of polyploidization or entire genome fusions during interspecies hybridizations (Renny-Byfield and Wendel, 2014) and, thus, contain multiple SUMO E2 conjugase genes (Novatchkova et al, 2012). Two other technical exceptions are zebrafish (Dana rerio; Nowak and Hammerschmidt, 2006) and rice (Oryza sativa; Nigam et al, 2008), which contain two nearly identical SUMO E2 conjugase genes that are apparent products of recent gene duplications.…”
mentioning
confidence: 99%
“…Major molecular chaperones such as Hsp101 (Queitsch et al 2000), Hsp70 (Lee and Schöffl 1996), and small Hsp (Kim et al 1997) have been reported to confer thermotolerance, but co-chaperones have not been well characterized. Although transcription levels of Hsp90 co-chaperones Hop and FKBP are induced by heat stress (Zhang et al 2003;Aviezer-Hagai et al 2007), only FKBP has a chaperone property (Bose et al 1996), and FKBP20 overexpression in yeast showed thermotolerance (Nigam et al 2008). Therefore, co-chaperones that exhibit chaperone activity may confer thermotolerance to cells.…”
Section: Discussionmentioning
confidence: 99%